Consensus statement on the use of high sensitivity cardiac troponins - Jardine, RM; Dalby, AJ; Klug, EQ; Vermaak, WH; White, HD; Badenhorst, JCW; Osrin, LB; du Plessis, M; Naicker, JT; Rambau, PD; et al. (SA Heart Journal, 2017)
The increased sensitivity of high sensitivity cardiac troponin assays comes at a cost of decreased specificity, and “false positive” diagnosis of acute coronary syndromes has made clinicians wary of their use, fearing unnecessary hospitalisations, angiography and revascularisation. The Ethics and Guidelines Standing Committee of SA Heart Association convened a meeting of cardiologists, chemical pathologists, emergency medicine specialists and industry representatives to discuss the role of high sensitivity troponin (hsTn) testing. An international expert provided guidance, and this Consensus Statement is the product of that meeting. It is recommended that hsTn assays be widely adopted as the preferred biomarker for diagnosis of myocardial infarction. Pathology laboratories will standardise the units of measurement and the reporting of results. Rules for interpretation of results and algorithms for their application are provided. Separate algorithms apply to troponin T and troponin I, and the several troponin I assays on the market each have different numerical values. Use of high sensitivity troponin assays will result in earlier diagnosis of myocardial infarction, more reliable ruling out of myocardial infarction, and shortening of chest pain triage (to 4 hours), compared to former assays.